(untitled) (Journal of Economic Research & Business Administration, 2022)
The development of the housing market of the Republic of Kazakhstan in 2020 was predetermined by important factors – the unfavorable economic situation caused by COVID-19 and the spread of this virus. The main purpose of this article is to analyze and assess the dynamic development of the housing market of the Republic of Kazakhstan in the context of COVID-19 when compared with the crisis year of 2014 and analyze the potential consequences. Thanks to the collection and analysis of statistical data and continuous monitoring of the housing market, conclusions were drawn about serious changes, both in market directions and in systemic changes in the state housing policy. In the article, using methods of comparative analysis, trends in the development of the housing market are identified, key factors influencing the annual dynamics of real estate prices are identified; their quantitative impact was assessed using correlation analysis and econometric models of the impact of these factors on the average housing price by the population were evaluated and the permissible consequences of restrictions and measures introduced in connection with the pandemic were determined. Recommendations are proposed to support the housing market of the Republic of Kazakhstan, stimulating the development and coverage of all market entities. The results obtained will be useful to researchers, organizers of investment projects and representatives of government bodies. Key words: Housing market, COVID-19, housing prices, government regulation, mortgages.